Diversity of Oil Palm Seedlings Jambi Accessions Exhibits Physiology Responses Differently During a Waterlogged - Evan Vria Andesmora; Hamim; Sulistijorini; Triadiati Triadiati (Jurnal Ilmu Pertanian Indonesia, 2025)
Cultivated oil palm is commonly found in several ecosystems with different topographies, including riparian areas. This ecosystem is expected to affect the morphology and physiology of oil palms. In addition, oil palm habitats in riparian or flooded ecosystems will experience anaerobic respiration. Indonesia has the potential to access quality palm oil that can be used for cultivation. This study aimed to determine which oil palm accessions could adapt physiologically to the duration of waterlogging. The accession of oil palm seedlings from Jambi tested were Merangin, Tebo, Muara Jambi, Tanjung Jabung, and Simalungun. The research design was to treat waterlogging in a greenhouse and then analyze the plant growth and physiology. Waterlogging was given for two, four, and six weeks. The results showed that the accession of oil palm seedlings and the duration of waterlogging affected photosynthesis rate, transpiration rate, and stomatal conductance. Growth parameters, i.e., fresh weight, dry weight, and root/shoot ratio, were significantly different in accession and waterlogging duration. In conclusion, accessions from Tebo and Merangin can adapt to waterlogging. Keywords: Merangin accession, photosynthesis rate, stomatal conductance, Tebo accession